The relationship between work environment on job satisfaction at Terreal Malaysia Sdn Bhd / Nurul A’isyah Ayob - Ayob, Nurul A’isyah (Faculty of Business and Management, 2019)
Work environment become one of the most important factors that affect employee job satisfaction. The work environment can implicate the social relation at workplace and also maintain the relationship between the employees and employer. A happy and satisfied employees is the biggest asset of any organization. Moreover, high productivity of organization is depend on the level of employees’ satisfaction and work environment become the most important factor which influence the employees job satisfaction. Hence, the purpose of this research is to identify the relationship between work environment on job satisfaction at Terreal Malaysia Sdn Bhd, Kluang, Johor. This research is quantitative research which had used the questionnaire as the instrument for collection of data. In this research, a total of 136 respondents which was derived from the total population of 210 elements. Sample selection was based on probability sampling method. This research adapted by using Statistical Package for the Social Science (SPSS) Version 22 Software. By using SPSS, numerous test were used such as reliability analysis, frequency distribution, descriptive analysis, Pearson correlation analysis and multiple regression. In conclusion, the results indicated that work environment which include relationship with co-worker and work-life balance are related to job satisfaction while safety and motivation are not related to job satisfaction.